2016
DOI: 10.3390/ijerph13030324
|View full text |Cite
|
Sign up to set email alerts
|

Association of Geography and Ambient Air Pollution with Urine Metal Concentrations in Six US Cities: The Multi-Ethnic Study of Atherosclerosis

Abstract: We investigated the associations of urinary concentrations of antimony, cadmium, tungsten and uranium with geographic locations and with ambient air pollution in 304 adults in the Multi-Ethnic Study of Atherosclerosis from six US cities. After adjustment for sociodemographics, body mass index, and smoking status, urinary cadmium was the highest in Winston-Salem among all study sites (the geometric mean [GM] in Winston-Salem was 0.84 µg/L [95% confidence interval (CI) 0.57–1.22]). The adjusted GMs of urinary tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Another interesting area of future research is the role of joint exposures in atherosclerosis. It is important to evaluate mixtures of metals as metals co-occur together [154, 155]. While several of the retrieved studies adjusted the regression models for other metals, statistical methods to comprehensively tackle mixtures of compounds are needed.…”
Section: General Discussion and Needs For Future Epidemiologic Researchmentioning
confidence: 99%
“…Another interesting area of future research is the role of joint exposures in atherosclerosis. It is important to evaluate mixtures of metals as metals co-occur together [154, 155]. While several of the retrieved studies adjusted the regression models for other metals, statistical methods to comprehensively tackle mixtures of compounds are needed.…”
Section: General Discussion and Needs For Future Epidemiologic Researchmentioning
confidence: 99%
“…32 Urinary tungsten levels have been associated with PM 2.5 previously in MESA. 33 Some prior but limited evidence has related tungsten with cardiovascular outcomes. In NHANES, urinary tungsten levels were associated with stroke prevalence, 34 composite cardiovascular and cerebrovascular disease, 35 and higher self-reported CVD.…”
Section: Discussionmentioning
confidence: 99%
“…MESA Air investigators found a positive association of PM 2.5 levels with urinary tungsten and also some evidence of an association with urinary uranium but did not see any relationship to urinary cadmium or antimony. 22 MESA Air researchers also found a moderate correlation between air pollution and noise. 23 …”
Section: B Exposure Assessment / Air Pollution Modelingmentioning
confidence: 98%